TITIK TEMU SUFISME DAN PSIKOLOGI; KAJIAN ATAS QS. AL-FAJR: 27-30 - Muhsin (IAIN Madura, 2021)
The problem that this paper would like to answer is whether there are similarities between sufism and psychology in the discussion of soul. So far, sufism is known on the purification of the soul as its material object. To examine the soul, I observe the interpretation of Q.S al-Fajr verses 27-30. The method used is the tahlili method. This means to know how Islam understands the soul then to relate it with the explanation of soul according to psychology. Based on the results of this study, I reveal that there is a meeting point between sufism and psychology. Referring to the poems of Ibn Athailah al-Iskandari, I see similarities between him and secular psychologists such as Aristotle and Plato. I also conclude that considering the soul as their common object material. (Permasalahan yang akan dijawab dalam tulisan ini yaitu apakah terdapat persamaan antara sufisme dan psikologi dalam pembahasan kejiwaan. Selama ini sufisme yang dikenal dengan penyucian diri menjadikan jiwa sebagai obyek materialnya. Untuk mengkaji jiwa, penulis melihat penafsiran Q.S al-Fajr ayat 27 – 30 dengan metode tahlili. Ini dimaksudkan untuk melihat pemahaman Islam terhadap jiwa kemudian mengaitkannya dengan penjabaran dari jiwa menurut ilmu psikologi. Berdasarkan hasil penelitian ini, penulis menemukan bahwa terdapat titik pertemuan antara sufisme dan psikologi. Mengacu kepada Syair-Syair Ibn Athailah al-Iskandari, misalnya, penulis melihat ada persamaan dengan para psikolog umum seperti Aristoteles dan Plato. Dengan demikian, terdapat persamaan antara sufisme dan psikologi karena sama-sama menjelaskan tentang jiwa).